Energy intake and expenditure of professional soccer players of the English Premier League: Evidence of carbohydrate periodization - Anderson, L.; Orme, P.; Naughton, R. J.; Close, G. L.; Milsom, J.; Rydings, D.; O'Boyle, A.; Di Michele, R.; Louis, L.; Hambly, C.; Speakman, J. R.; Morgans, R.; et al. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
In an attempt to better identify and inform the energy requirements of elite soccer players, we quantified the energy expenditure (EE) of players from the English Premier League (n = 6) via the doubly labeled water method (DLW) over a 7-day in-season period. Energy intake (EI) was also assessed using food diaries, supported by the remote food photographic method and 24 hr recalls. The 7-day period consisted of 5 training days (TD) and 2 match days (MD). Although mean daily EI (3186 ± 367 kcals) was not different from (p > .05) daily EE (3566 ± 585 kcals), EI was greater (p < .05) on MD (3789 ± 532 kcal; 61.1 ± 11.4 kcal.kg-1 LBM) compared with TD (2956 ± 374 kcal; 45.2 ± 9.3 kcal.kg-1 LBM, respectively). Differences in EI were reflective of greater (p < .05) daily CHO intake on MD (6.4 ± 2.2 g.kg-1) compared with TD (4.2 ± 1.4 g.kg-1). Exogenous CHO intake was also different (p < .01) during training sessions (3.1 ± 4.4 g.h-1) versus matches (32.3 ± 21.9 g.h-1). In contrast, daily protein (205 ± 30 g.kg-1, p = .29) and fat intake (101 ± 20 g, p = .16) did not display any evidence of daily periodization as opposed to g.kg-1, Although players readily achieve current guidelines for daily protein and fat intake, data suggest that CHO intake on the day before and in recovery from match play was not in accordance with guidelines to promote muscle glycogen storage.